Interaction of the antimicrobial peptide ∆M3 with the Staphylococcus aureus membrane and molecular models (2021)
ABSTRACT: Staphylococcus aureus is one of the most pathogenic bacteria; infections with it are associated with significant morbidity and mortality in health care facilities. Antimicrobial peptides are a promising next generation antibiotic with great potential against bacterial infections. In this study, evidence is presented of the biological and biophysical properties of the novel synthetic peptide ΔM3. Its antimicrobial activity against the ATCC 25923 and methicillin-resistant S. aureus strains was evaluated. The results showed that ΔM3 has activity in the same μM range as vancomycin. Biophysical studies were performed with palmitoyloleoylphosphatidylglycerol and cardiolipin liposomes loaded with calcein and used to follow the lytic activity of the peptide by fluorescence spectroscopy. On the other hand, ΔM3 was induced to interact with molecular models of the erythrocyte membrane buil-up of dimiristoylphosphatidylcholine and dimyristoylphosphatidylethanolamine, representative lipids of the outer and inner monolayers of the human erythrocyte membrane, respectively. The capacity of ΔM3 to interact with the bacteria and erythrocyte model membranes was also evaluated by X-ray diffraction and differential scanning calorimetry. The morphological changes induced by the peptide to human erythrocytes were observed by scanning electron microscopy. Results with these techniques indicated that ΔM3 interacted with the inner monolayer of the erythrocyte membrane, which is rich in anionic lipids. Additionally, the cytotoxic effects of ΔM3 on red blood cells were evaluated by monitoring the hemoglobin release from erythrocytes. The results obtained from these different approaches showed ΔM3 to be a non-cytotoxic peptide with antibacterial activity